2009
DOI: 10.1080/09637480902787601
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extrusion conditions and formulation of spaghetti enriched with full-fat soy flour based on the cooking and color quality

Abstract: The influence of full-fat soy flour (FFSF) 0-27.0 g/100 g, water content 31.0-35.0 g/100 g and extrusion conditions on the cooking and color characteristics of spaghetti was investigated. The process was performed with a speed of 10-40 rpm and a water circulating temperature of 35-70 degrees C. The results showed that adding FFSF causes decreases (P< or =0.05) in cooking time, cooking weight, intensity and hue characteristics. However, the cooking loss and saturation of spaghetti increased (P< or =0.05). The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…Cooking time was greatest for the control spaghetti, closely followed by the spaghetti containing corn flour or oat flour, intermediate for spaghetti containing lentil or pinto bean flour and least for spaghetti containing flaxseed flour or soybean flour (Table 3). These results are in agreement with Nasehi et al (2009), Manthey & Dash (2010 and Petitot et al (2010) who also reported that spaghetti fortified with soybean flour, flaxseed flour and bean flour, respectively, had a shorter cooking time than did the control spaghetti. However, other authors have reported that pasta containing legume flours such as lentil, soybean and bean flours had similar or longer cooking time than the standard spaghetti due to its high protein content (Zhao et al, 2005;Gallegos-Infante et al, 2010).…”
Section: Cookingsupporting
confidence: 91%
See 2 more Smart Citations
“…Cooking time was greatest for the control spaghetti, closely followed by the spaghetti containing corn flour or oat flour, intermediate for spaghetti containing lentil or pinto bean flour and least for spaghetti containing flaxseed flour or soybean flour (Table 3). These results are in agreement with Nasehi et al (2009), Manthey & Dash (2010 and Petitot et al (2010) who also reported that spaghetti fortified with soybean flour, flaxseed flour and bean flour, respectively, had a shorter cooking time than did the control spaghetti. However, other authors have reported that pasta containing legume flours such as lentil, soybean and bean flours had similar or longer cooking time than the standard spaghetti due to its high protein content (Zhao et al, 2005;Gallegos-Infante et al, 2010).…”
Section: Cookingsupporting
confidence: 91%
“…These results are in agreement with Nasehi et al . (), Manthey & Dash () and Petitot et al . () who also reported that spaghetti fortified with soybean flour, flaxseed flour and bean flour, respectively, had a shorter cooking time than did the control spaghetti.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…During the processing, the incorporation of soy flour to the cassava dough resulted in an increase in protein content. The results are in accordance those of [18]. Mridula et al [19] have also shown that the substitution of wheat flour for peanut seed, which is a legume, improves the protein content of pasta.…”
Section: Effect Of Variables On the Protein Content Of Formulationssupporting
confidence: 85%
“…These results are similar to the results reported by Nasehi et al . () where fortification of full fat soya flour significantly decreased cooking time and cooked weight and increased cooking loss of spaghetti. Zhao et al .…”
Section: Resultsmentioning
confidence: 99%